Feasibility pilot of a novel coaching intervention to optimize cannabis use for chronic pain management among Veterans - Kevin F. Boehnke; Gabrielle Bowyer; Jenna McAfee; Tristin Smith; Catherine Klida; Vivian Kurtz; Evangelos Litinas; Poonam Purohit; Anne Arewasikporn; Dana Horowitz; Laura Thomas; Jennifer Eckersley; et al. (Journal of Cannabis Research)
Abstract Introduction Chronic pain is common among Veterans, some of whom use cannabis for pain. We conducted a feasibility pilot study of a novel coaching intervention to help Veterans optimize use of medical cannabis products for pain management (NCT06320470). Methods The intervention drew from scientific literature, consultation with cannabis experts, Veteran input via a Community Advisory Board, and tenets of motivational interviewing. Participants were Veterans with chronic pain who endorsed current use or interest in using cannabis for pain management. Participants received up to 4 individual coaching sessions via videoconference, spaced approximately 2 weeks apart. We assessed feasibility (adherence, satisfaction, acceptability) and preliminary effects on pain symptoms 14 weeks after baseline. The primary outcome was the Patient Global Impression of Change (PGIC), and exploratory outcomes included domains from the Patient-Reported Outcomes Measurement Information System (PROMIS)-29. Results Of 22 enrolled participants, 17 attended 4 coaching sessions, 2 attended 3 sessions, and 2 attended 2 sessions. Among those who completed end of intervention surveys (16/21), 87.5% were very or completely satisfied with the intervention and 81.3% rated coaching as very or extremely helpful. All participants reported improvement on the PGIC, with 63% reporting much or very much improvement. Participants reported statistically significant decreased pain intensity (7.1/10 vs. 5.7/10) and pain interference (T-score 66.3 vs. 61.8), and increased social satisfaction (T-score 41.4 vs. 44.3). Participants noted helpful intervention factors, including co-developing a personalized plan, discussing questions/concerns, and trying different approaches to cannabis-based treatment. Conclusions In this feasibility pilot study of coaching on cannabis use for chronic pain among Veterans, participants were satisfied with the intervention and reported clinically significant improvements in pain symptoms. Our results support evaluating this intervention in a larger, efficacy trial.